IMPLEMENTATION OF CONTINUOUS QUALITY IMPROVEMENT (CQI) IN ENGINEERING MATHEMATICS COURSE AT POLITEKNIK KOTA KINABALU - Adeline Ahyun; Helley Halen; Ayuzi Binti Taib (Jurnal Penyelidikan Sains Sosial, 2023)
The main purpose of this study is to identify the impact of Continuous Quality Improvement (CQI) implementation on End-of-Chapter (EOC) coursework assessment for Engineering Mathematics 1 course in Politeknik Kota Kinabalu, Sabah. The research design is descriptive quantitative by using data review strategy. The data acquisition method is done by collecting the mean score of students’ achievements in EOC assessment by sessions and classes for each CQI that has been implemented. The respondents involved were first semester engineering students of Politeknik Kota Kinabalu. Data were analyzed using SPSS version 26 to obtain the mean achievement score of the students’ EOC assessment by session with implemented CQI. The results of the study found that Aim Peer Collaborative is the best proposed CQI with the highest mean score achievement. Aim Peer Collaborative shall remain its implementation for EOC in future sessions.